Comparing behavioural responses of Greylag Geese Anser anser and Egyptian Geese Alopochen aegyptiaca to human disturbance in an urban setting - Hohmann, Rieke; Woog, Friederike (Wildfowl, 2021)
When animals first colonise urban areas, they may perceive disturbance from humans and their pets as a novel form of predation risk. Adaptation to predation risk is important in an evolutionary sense: caution could be beneficial for reducing the risk of injury and mortality; on the other hand, reacting too soon and too often can cause stress, costs energy and may lower survival. This study compares the extent of tolerance to human disturbance in two introduced but established waterfowl species, Greylag Geese Anser anser (Anserinae) and Egyptian Geese Alopochen aegyptiaca (Tadorninae). After their recent colonisation of the city of Stuttgart in southwest Germany, Greylag Geese first hatched a brood in 1995, while Egyptian Geese only latterly colonised the city (first successfully fledged brood in 2010), but subsequently showed exponential population increase. There are many potential reasons for this; they may have a broader ecological niche (i.e. are able to use a wider array of available nesting sites), and have larger broods with higher fledging rates, but Egyptian Geese may also show higher tolerance towards disturbance than Greylag Geese in an urban setting. We investigated the last of these hypotheses by comparing variation between the two species in their reaction to disturbance stimuli between 5 June and 22 August 2018. Our behavioural observations showed that Egyptian Geese reacted to disturbance stimuli > 50% more frequently than Greylag Geese, and with more intense behaviours. In addition to species-specific differences, we found that reaction to disturbance also varied with location, the type of disturbance, social status, time of day and ambient temperature. Both species reacted most strongly (i.e. were alerted or displaced at greater distances) when disturbed by dogs. Egyptian Geese were generally more cautious than Greylag Geese to equivalent stimuli from human presence. Such cautiousness may, in addition to ecological differences, partly explain the greater success of Egyptian Geese as an invading species in novel environments. Alternatively, this difference between the two species may reflect a longer habituation period, or perhaps genetic adaptation to disturbance stimuli by Greylag Geese.